2021
DOI: 10.1093/plcell/koab022
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation in plant telomere length is associated with flowering time

Abstract: Telomeres are highly repetitive DNA sequences found at the ends of chromosomes that protect the chromosomes from deterioration during cell division. Here, using whole genome re-sequencing and terminal restriction fragment assays, we found substantial natural intraspecific variation in telomere length in Arabidopsis thaliana, rice (Oryza sativa), and maize (Zea mays). Genome-wide association study (GWAS) mapping in A. thaliana identified 13 regions with GWAS-significant associations underlying telomere length v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 86 publications
1
60
0
Order By: Relevance
“…We generated full-length cDNA sequences using the ONT platform and used these reads to predict protein coding genes in Vmac and Voxy and found 48,647 and 50,621 respectively (Table1). We annotated the telomeres (AAACCCT), which revealed Vmac has longer telomeres (∼12 kb) than Arabidopsis (∼3 kb) [32] (Figure S5). In addition, we found centromeres with higher order repeats and base arrays of 124 bp (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…We generated full-length cDNA sequences using the ONT platform and used these reads to predict protein coding genes in Vmac and Voxy and found 48,647 and 50,621 respectively (Table1). We annotated the telomeres (AAACCCT), which revealed Vmac has longer telomeres (∼12 kb) than Arabidopsis (∼3 kb) [32] (Figure S5). In addition, we found centromeres with higher order repeats and base arrays of 124 bp (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous analysis of telomere length variation in 653 natural A. thaliana accessions 324 indicated that genotypes with longer telomeres flower earlier 25 . These experiments provided preliminary evidence that telomere length may be an adaptive trait in plants and suggested an intriguing link between life history strategies and chromosome structure.…”
Section: Discussion 262mentioning
confidence: 98%
“…Overall, these GxE interactions indicate that telomere length variation can exact environment-dependent fitness costs. Thus, the natural genetic variation for telomere length previously observed in plants 25 may be maintained through varying selection pressures imposed by different environmental conditions.…”
Section: Evidence Of Gxe Interactions Leading To Life History Trade-offsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant senescence is obviously distinguished from the aging in animals, which is mainly reflected in the decline of assimilation and the nutrients redistribution. Moreover, the telomere length has been recently demonstrated to be positively related to early flowering time, while longer telomere in animals usually means longevity (Choi et al, 2021 ). Therefore, appropriate timing of leaf senescence is of immense importance for plant growth and especially for crop yield and quality.…”
Section: Discussionmentioning
confidence: 99%